2018
DOI: 10.1186/s12967-018-1529-0
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of the DNA methylation levels of the ADRB3 gene in leukocytes is related with serum folate in eutrophic adults

Abstract: BackgroundDNA methylation has been evidenced as a potential epigenetic mechanism related to various candidate genes to development of obesity. Therefore, the objective of this study was to evaluate the DNA methylation levels of the ADRB3 gene by body mass index (BMI) in a representative adult population, besides characterizing this population as to the lipid profile, oxidative stress and food intake.MethodsThis was a cross-sectional population-based study, involving 262 adults aged 20–59 years, of both genders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…It is well documented that folate in one-carbon metabolism plays a central role in the synthesis, repair, and methylation of DNA, where it acts as a methyl donor. Folate homeostasis disruption could affect methylation potential through DNA gene hyper- or hypomethylation reactions and lead to gene transcription alterations (overexpression and/or gene silencing) [50, 51]. In our discovery group, genome-wide DNA methylation analysis identified that folate was significantly associated with DNA methylation of antioxidant genes NUDT15 and TXNRD1, both of which were hypermethylated in the MCI group.…”
Section: Discussionmentioning
confidence: 96%
“…It is well documented that folate in one-carbon metabolism plays a central role in the synthesis, repair, and methylation of DNA, where it acts as a methyl donor. Folate homeostasis disruption could affect methylation potential through DNA gene hyper- or hypomethylation reactions and lead to gene transcription alterations (overexpression and/or gene silencing) [50, 51]. In our discovery group, genome-wide DNA methylation analysis identified that folate was significantly associated with DNA methylation of antioxidant genes NUDT15 and TXNRD1, both of which were hypermethylated in the MCI group.…”
Section: Discussionmentioning
confidence: 96%
“…In the study conducted by Oliveira et al [38], it was observed that higher levels of methylation were not associated with lipid profile and oxidative stress, when the individuals were separated according to eutrophic, overweight and obesity classification, the study used the analysis of methylation levels by real-time PCR method, MS-HRM, in addition in the present study the whole sample was used.…”
Section: Discussionmentioning
confidence: 96%
“…This information and other information about the sampling are further detailed in recently published studies [ 39 , 40 ], with the exception of the levels of methylation of the LPL and MTHFR gene, the calculated values of LDL-C in accordance with Martin [ 13 ] and the stratification of the sample according to the LDL-C values.…”
Section: Methodsmentioning
confidence: 99%